Are Absence and Limbic Seizures Mutually Exclusive?: An Experimental Approach to Enigmatic Clinical Concept - Onat, Filiz Yılmaz; Eşkazan, Esat (Journal of Pediatric Epilepsy, 2021)
The impressive advances in the several disciplines including neurophysiology, molecular biology, neuroimmunology, neurogenetics, neuroimaging, and neuropharmacology of epilepsies have been stimulating a mutual interaction among basic scientists, clinicians, and professionals from other disciplines, leading to the identification of clinical questions and then the design of basic science paradigms to test enigmatic clinical issues. Based on a clinical observation that the coexistence of genetic (idiopathic) generalized typical absence and mesial temporal lobe epilepsy in the same patient is extremely rare and debatable, we addressed the rare coexistence in the same individual, designed an experimental approach to test the validity of this clinical concept and to study the underlying mechanisms involved. Here we presented evidence of a mutual cross-interaction in the circuits involved in typical absence and temporal lobe epilepsy. This article delineates a phenomenological picture and comprehends a theoretical understanding of a mutual cross-interaction in typical absence as a representative of genetic generalized epilepsies and limbic epilepsy in which seizures often start from the mesial temporal lobe.
Keywords: limbic seizures; absence seizures; clinical concepts